Dilbag Singh and Paramjit Singh (Farmers) - Madyapur, Punjab, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
The two farmers Dilbag Singh and Paramjit Singh talk about the changes in weather and how they are trying to adapt. Both have had to switch to hybrid seeds that require less pesticides and water, but still produce higher yields. Paramjit is also trying to grow poplar trees to complement his agriculture production. Poplar trees need less water than other trees and grow in 4 years making it an additional income without affecting the yields of rice.